Supracricoid partial laryngectomy with cricohyoidoepiglottopexy: Surgical technique illustrated in the anatomy laboratory. Issue 6 (June 2015) - Holsinger, F. Christopher; Tomeh, Chafeek; Moore, Michael W.; Yan, Wang; Chen, Crystal; Laccourreye, Ollivier
<x xml:space="preserve">Abstract</x> Background.Methods.Results.Conclusion. © 2014 Wiley Periodicals, Inc. Head Neck 37: 906–908, 2015